Prospective Teachers’ Awareness of Teacher Certification for Quality Assurance in Nigerian Education System - Olokooba, Issa Nasiru; Abdulsalam, Alliyu Ayodele; Badamas, Omoshalewa Lasbat (International Journal of Educational Management, 2022)
Teaching is a profession that produces other professions all over the world in which Nigeria is not an exception. The profession is adequately certified, regulated and licensed by Teacher Registration Council of Nigeria to ensure the quality and standard in the system. The prospective teachers of teacher educational institutions are important stakeholders trained to facilitate and enhance the effective teaching and learning processes in the in the classrooms but how far are the teachers aware of teacher certification. It becomes imperative to assessed prospective teachers’ awareness of teacher certification for quality assurance in the education system. The objectives of the study were to investigate prospective teachers’ awareness of teacher certification, obligations of teachers under TRCN and, rights and privileges of registered teachers with TRCN for quality assurance in the sector. A descriptive survey research design was adopted for the study. A purposive sampling technique was employed to select three hundred students in teacher educational institutions in Kwara State. A researcher-design questionnaire was used for data collection. The data collected were analysed using percentage and means ranking. The findings of the study showed that prospective teachers were aware of some of the activities of the TRCN towards teacher certification and obligations of teachers registered under TRCN. The finding of the study also revealed that prospective teachers were not aware of rights and privileges of registered teachers with TRCN for quality assurance in the education system. Based on the findings, it was recommended among others that prospective teachers should be provided with information and enlightenment about rights and privileges of registered teachers with TRCN. This serves as motivation and encouragement to the teachers.